Financial Sector Development and Poverty Reduction in Namibia - Kandjii, Fabiola Tjikari (Graduate School of Business (GSB), 2021)
Among other challenges, it can be argued that poverty remains the greatest challenge facing the developing countries, particularly for Sub-Saharan countries. A significant proportion of people in the developing world are severely affected by poverty. In 2013 it was estimated that 787 million of the world population lived in severe poverty (World Bank, 2016). Moreover, Sub-Saharan Africa accounts for half of the population who are severely affected by poverty. Using Namibia as a case study and data sets from 1991 to 2017, this research investigates how financial development impacts on poverty reduction in the country. The study employed the Johansen Cointegration Procedure and Vector Error Correction Model to test the data. The data was obtained from the World Development Indicators and the Namibia Central Bank. The main findings suggest that financial development is important for poverty reduction in the Namibian context, and has a positive and significant effect on poverty reduction. Further, there was a unidirectional causality between financial development and poverty. The Johansen cointegration results reported three cointegration equations amongst the variables, confirming a long-run cointegration relationship between financial sector development and poverty reduction. Interestingly, the per capita GDP is negatively associated with the poverty measure. The study recommends the government to focus on policies that stimulate credit to the private sector. In terms of trade openness, policies should aim at improving and strengthening fair bilateral and multilateral trade, as well as promoting regional trade in order to grow trade volumes.